PENGARUH CURRENT RATIO, PERPUTARAN PIUTANG, NET PROFIT MARGIN, KEBIJAKAN HUTANG, TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER GOODS DAN SEKTOR ANEKA INDUTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Laoli, Irene Yuniman; Zamili, Melfi Shania Putri; Tambunan, Elsalonika Br; Pasaribu, Laurine Aurelia Sorcha; Purba, Mohd. Nawi (2021)
The purpose of this study is to provide and increase knowledge for readers and analyze the effect of CR, Accounts Receivable Turnover, Net Profit Margin, Debt to equity ratio on Market to Book Ratio in Consumer Goods and Miscellaneous Industry Sectors listed on the Indonesia Stock Exchange in the 2016-2019 period. The investigate populace utilized was 98, the investigate test was 40. The inquire about strategy utilized quantitative insights. The information investigation procedure utilized the classical suspicion test. Theory testing is surveyed by different direct relapse, T test, and F test.The comes about of the speculation test of the coefficient of assurance gotten an Adjusted R Square (R2) esteem of 33,2%, so it can be said that the variable CR (X1), accounts receivable turnover (X2) ), NPM (X3), and debt to equity ratio(X4) simultaneously affect Market to Book Ratio (Y) by 33,2% and the remaining 66,8% is influenced by other variables not found in this study.